Features of the course urate nephrolithiasis, comorbid with the metabolic syndrome - A. O. Hubar; M. A. Dovbysh; O. M. Mischenko; I. M. Dovbysh (Zaporozhye State Medical University, 2022)
The aim of the work is to study the peculiarities of the course of urate nephrolithiasis and urate nephrolithiasis comorbid with metabolic syndrome. Materials and methods. Clinical and laboratory data of 183 patients. The control group of patients with urate nephrolithiasis received traditional therapy. The patients of the main group with urate nephrolithiasis comorbid with metabolic syndrome took quertin and traditional therapy, as well as popular medical drugs that correct metabolic processes. Clinical laboratory, biochemical, ultrasound, radiological, radioisotope, immunoenzymatic, and physical-chemical methods were used. Results. The pain was more intense in patients with urate nephrolithiasis than in patients with urate nephrolithiasis comorbid with metabolic syndrome. Manifestations of the inflammatory process increased in patients with urate nephrolithiasis comorbid with metabolic syndrome, and concomitant diseases intensified the excretion of stone-forming compounds. Metaphylaxis with quertin against the background of commonly accepted drugs that correct metabolic processes had a positive effect on the course of urate nephrolithiasis comorbid with metabolic syndrome and contributed to the reduction of stone formation relapse. Conclusions. In-depth diagnosis of metabolic processes can help the doctor to correctly determine the differentiated tactics of examination and treatment, as well as to prevent possible complications in a timely manner.